Assessment measures of an ensemble classifier based on the distributivity equation to predict the presence of severe coronary artery disease - Rak, Ewa; Szczur, Adam; Bazan, Jan G.; Bazan-Socha, Stanisława (Zielona Góra: Uniwersytet Zielonogórski)
The aim of this study is to apply and evaluate the usefulness of the hybrid classifier to predict the presence of serious coronary artery disease based on clinical data and 24-hour Holter ECG monitoring. Our approach relies on an ensemble classifier applying the distributivity equation aggregating base classifiers accordingly. Such a method may be helpful for physicians in the management of patients with coronary artery disease, in particular in the face of limited access to invasive diagnostic tests, i.e., coronary angiography, or in the case of contraindications to its performance.
Keywords: ensemble methods; distributivity equation; aggregation functions; accuracy; precision; sensitivity; CAD; Holter ECG